KOMPOSISI KIMIA DAN SIFAT FUNGSIONAL PATI JAGUNG BERBAGAI VARIETAS YANG DIEKSTRAK DENGAN PELARUT NATRIUM BIKARBONAT - Nur Alam Nur Alam; Nurhaeni Nurhaeni (Universitas Tadulako, 2008)
The aim of this experiment was to analyse chemical composition and functional properties of corn starch from various corn varieties extracted with natrium bicarbonat solution. Corn kernels of N35, Sticky corn, yellow Srikandi and yellow local varieties were processed into starch. The starch was extracted with 1% natrium bicarbonat solution (1:10 [w/v]). Starch of commercial corn was used as a control. This experiment used Randomized Block Design with three replications. Results of this experiment indicated that the highest starch, amylose, fibre and free fatty acid contents were obtained at starch of yellow local variety; and the highest sugar, protein and lypide contents were found at yellow Srikandi variety, whilst the highest ash content was achieved at N35 variety. Starch of sticky corn possessed the lowest amylose content, but had the highest amylopectine content. The highest water absorbtion and solution rate were obtained at starch of yellow local variety. Furthermore, the highest oil absorbtion rate was achieved at starch of sticky corn variety. Corn starch extracted with natrium bicarbonat solution had a lower quality compared to commercial corn starch, and therefore the corn starch recovered here apparently should not be recommended as a food source.